Very Severe and Refractory Noninfectious Cystitis in Patients with Systemic Lupus Erythematosus: Potential Role of Rituximab Therapy - Vanessa Ocampo-Piraquive; Inés Mondragón-Lenis; Juan G. De los Rios; Carlos A. Cañas (Case Reports in Rheumatology)
Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease with various clinical manifestations, including, rarely, a form of interstitial cystitis (lupus cystitis, LC). LC can be asymptomatic and usually has discrete symptoms that improve with conventional therapies available for SLE and/or typical interstitial cystitis. A very severe and refractory form is rarely described. In this study, we present four patients with SLE and a very severe form of noninfectious cystitis refractory to the different forms of treatment described. The clinical descriptions of the cases, demographic factors, manifestations associated with SLE, and clinical and paraclinical manifestations related to cystitis, treatments, and outcomes are provided. A proposal for the pathogenesis of this condition is based on the common findings of these patients, including the fact that three were in SLE remission and all four receiving rituximab as induction and/or maintenance therapy.